2005
DOI: 10.1128/mcb.25.23.10391-10406.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Ubiquitination and Sumoylation on Overlapping Lysine Residues Mediate NF-κB Activation by the Human T-Cell Leukemia VirusTax Oncoprotein

Abstract: The transcription factor NF-B is critical for the induction of cancer, including adult T-cell leukemia, which is linked to infection by human T-cell leukemia virus type 1 and the expression of its regulatory protein Tax. Although activation of the NF-B pathway by Tax involves its interaction with the regulatory subunit of the IB kinase (IKK) complex, NEMO/IKK␥, the mechanism by which Tax activates specific cellular genes in the nucleus remains unknown. Here, we demonstrate that the attachment of SUMO-1 to Tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
200
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(220 citation statements)
references
References 52 publications
20
200
0
Order By: Relevance
“…Recent studies have shown that Tax undergoes ubiquitination and sumoylation, and that these two modifications act coordinately to regulate Tax localization to nuclear bodies and recruitment of RelA and NEMO to activate NF-kBdependent gene expression (Lamsoul et al, 2005). Together with many prior reports, these studies reinforce the notion that many viruses utilize the NF-kB signaling pathway to manipulate the host apoptotic response to favor viral transformation and pathogenicity.…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectsupporting
confidence: 68%
“…Recent studies have shown that Tax undergoes ubiquitination and sumoylation, and that these two modifications act coordinately to regulate Tax localization to nuclear bodies and recruitment of RelA and NEMO to activate NF-kBdependent gene expression (Lamsoul et al, 2005). Together with many prior reports, these studies reinforce the notion that many viruses utilize the NF-kB signaling pathway to manipulate the host apoptotic response to favor viral transformation and pathogenicity.…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectsupporting
confidence: 68%
“…We also showed that Tax ubiquitylation on C-terminal lysines is critical for both Tax binding to IKK and for the nuclear translocation of RelA (Nasr et al, 2006). In addition, we and others showed that Tax is post-translationally modified by small ubiquitin-related modifier (SUMO) in the nucleus and that sumoylation is critical for the formation of RelA-enriched Tax nuclear bodies (Lamsoul et al, 2005;Nasr et al, 2006).…”
Section: Introductionmentioning
confidence: 77%
“…Ubiquitinated Tax resides in the cytoplasm and activates NF-B, whereas sumoylated Tax is located in nuclear bodies together with RelA (17,18). Ubiquitination and sumoylation of Tax occur on overlapping lysine residues of which lysines 263, 280, and 284 are critical for NF-B activation (17,18). In this report, we have monitored the subcellular localization of the individual endogenous IKK subunits in Tax-expressing T cells as well as HTLV-1-transformed cells.…”
mentioning
confidence: 99%
“…However, it is unclear exactly how Tax binding to IKK␥ triggers the catalytic activity of the IKKs. Several recent studies have reported that ubiquitination and sumoylation are important post-transcriptional regulators of Tax-mediated NF-B activation (17,18). Ubiquitinated Tax resides in the cytoplasm and activates NF-B, whereas sumoylated Tax is located in nuclear bodies together with RelA (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation